Acceptable outcomes after fundoplication—different views are held by patients, GPs, and surgeons. Issue 8 (25th April 2019) - Currie, Andrew C; Bright, Tim; Thompson, Sarah K; Smith, Lorelle; Devitt, Peter G; Watson, David I
SUMMARY: Antireflux surgery aims to improve quality of life. However, whether patients and clinicians agree on what this means, and what is an acceptable outcome following fundoplication, is unknown. This study used clinical scenarios pertinent to laparoscopic fundoplication for gastroesophageal reflux to define acceptable outcomes from the perspective of patients, surgeons, and general practitioners (GPs). Patients who had previously undergone a laparoscopic fundoplication, general practitioners, and esophagogastric surgeons were invited to rank 11 clinical scenarios of outcomes following laparoscopic fundoplication for acceptability. Clinicopathological and practice variables were collated for patients and clinicians, respectively. GPs and esophagogastric surgeons additionally were asked to estimate postfundoplication outcome probabilities. Descriptive and multivariate statistical analyses were undertaken to examine for associations with acceptability. Reponses were received from 331 patients (36.4% response rate), 93 GPs (13.4% response), and 60 surgeons (36.4% response). Bloating and inability to belch was less acceptable and dysphagia requiring intervention more acceptable to patients compared to clinicians. On regression analysis, female patients found bloating to be less acceptable (OR: 0.51 [95%CI: 0.29–0.91]; P  = 0.022), but dysphagia more acceptable (OR: 1.93 [95%CI: 1.17–3.21]; P  = 0.011). Postfundoplication estimation of reflux resolution was higher and that of bloating was lower for GPs compared to esophagogastric surgeons. Patients and clinicians have different appreciations of an acceptable outcome following antireflux surgery. Female patients are more concerned about wind-related side effects than male patients. The opposite holds true for dysphagia. Surgeons and GPs differ in their estimation of event probability for patient recovery following antireflux surgery, and this might explain their differing considerations of acceptable outcomes.